WOM Scouter: mobile service for reputation extraction from weblogs. (9th December 2008) - Kawamura, T.; Nagano, S.; Inaba, M.; Mizoguchi, Y.
In this paper, we introduce a mobile service that extracts reputations of a product from weblogs by cellular phones during shopping. In a mobile computing environment, it would be desirable for users to bind their real-world situation and useful information on the internet. However, the current typical devices for mobile computing, such as cellular phones, have small displays, limited operations, and narrow-band network. Thus, semantics can be useful in order to extract only the necessary information depending on the users' situation. Word-Of-Mouth (WOM) Scouter is an application for this purpose. If the user takes a photo of a product barcode on the package with a cellular phone camera, WOM Scouter first gets the product metadata (name, manufacturer, etc.) from the internet and collects blogs that review the product. Also, it analyses the blog contents with NLP techniques and ontologies. Then, it indicates the overall reputation (positive or negative), and other related products that are the subject of much discussion in the blogs. This paper illustrates each function of this service and a public experiment and evaluation at a real consumer electronics store and book-store in Tokyo in March 2006. This is a case of semantics use to provide an instant benefit in a mobile computing environment.